Effects of biodiesel from used frying palm oil on the performance, injection, and combustion characteristics of an indirect injection diesel engine - SAYIN, CENK (AMER CHEMICAL SOC, 2008)
In this study, biodiesel from used frying palm oil and its blends with diesel fuel were used in a four-cylinder, naturally aspirated indirect injection (IDI) diesel engine. Using petroleum-based diesel fuel (PBDF), biodiesel, and its blends, the engine performance, injection, and combustion characteristics were investigated over a range of engine speeds at full load. When the test engine was fueled with biodiesel and its blends, the brake specific fuel consumption increased slightly relative to PBDF due to its fuel properties and combustion characteristics. Biodiesel and its blends also showed a slight drop in the engine power with increased peak cylinder pressure and reduced ignition delay when compared to PBDF. In the all test conditions, the premixed combustion phase and the start of injection timing of biodiesel and its blends took place earlier than with PBDF.
Keywords: FUEL; EMISSIONS